Mixed monomolecular films with embedded dipolar groups on Ag(111) - Sauter, Eric; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2018)
We studied the application of the concept of embedded dipoles in monomolecular self-assembly to the Ag(111) substrate (evaporated film), using two different types of molecules with either pyrimidine groups embedded into aromatic backbones or ester groups embedded into aliphatic backbones as test systems. For both types of self-assembled monolayers (SAMs), the orientation of the embedded dipolar group was varied and the molecules with the oppositely oriented dipoles were combined together as mixed monolayers. In all cases, pronounced electrostatic effects of the embedded dipolar groups were observed, reflected, in a fully consistent manner, by the electrostatic shift in photoemission and by work function variation. The character and extent of these effects were, however, distinctly different for both types of SAMs, which was explained in context of structure-building interactions, specific orientation of the dipole moment of the embedded group with respect to the molecular backbone, and molecular orientation in general. The SAMs with the embedded pyrimidine group were found to be especially useful in context of the electrostatic interface engineering, allowing, in the case of Ag, a flexible tuning of the work function in the ∼0.85 eV range without changing the character of the SAM-substrate and SAM-ambient interfaces. An analogous behavior can also be expected for other substrates.